PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL DENGAN MEDIA PEMUTARAN FILM PADA MATERI KEHIDUPAN PRA AKSARA - Tri Widodo; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
To reduce verbalism, confusion of meaning and inappropriate perceptions of students towards the material provided by the teacher during the learning process, it is necessary to have a learning media in the form of teaching aids (models) as well as learning support facilities that support the times. This research is motivated by the desire to apply a contextual learning approach with film screening media to improve student learning outcomes in the subject matter of life in the pre-literacy period. This research is a classroom action research. The subjects were 32 students in VIIA class at SMP Negeri 6 Purworejo semester 1 of the 2020/2021 school year, consisting of 18 female students and 14 male students. This study aims to improve student learning outcomes. The implementation process is participatory collaborative with other teachers, and the principal which begins by conducting an initial fact-finding study then recycling which includes: (1) preparing plans, (2) carrying out actions, 3) observing (observation); (4) reflection. This research was conducted in two cycles, namely cycle I and cycle II.) Data collection techniques used: Test techniques, Observation, Documentation. Data analysis was carried out both quantitatively and qualitatively. The results of classroom action research by applying a contextual learning approach with film screening media can be seen from several activities carried out by students during the learning process. The initial evaluation result indicator is at least 75% of all students in the class meeting the complete learning target, the learning outcomes of students with a score of 61 and above in social studies learning. Conversely, if learning social studies history in lesson I has not been said to be complete, it will be continued in the next lesson. In learning I the success reached 68%. In learning II student learning outcomes have reached 70%, in learning II this meets the target of complete learning. According to the results of preliminary observations of 32 students, there were only 15 students who scored more than 70 (said complete) in their initial abilities in a proportion of 46.8%. After learning was held in cycle II, student learning outcomes in class had reached 30 students (93.8%) of all students in the class meeting the complete learning target, which means students scored 70 and above in learning.